The Bad Guys in the others?! - Blabey, Aaron ([New York, NY] : Scholastic Inc., 2022)
"OK. A lot of the stuff we said on the back of the last book was NOT TRUE. We now admit that The Bad Guys is WEIRD. We also admit that it features ALL the weird stuff we said it didn't. PLUS there's now a whole bunch of even weirder stuff involving an over-sharing bat, a really scary new character who lives in the woods, and a strangely confident little guy with a mullet. So, uh, don't relax, maybe FREAK OUT a little and have your MIND BLOWN by the BAD GUYS!"--
"First published by Scholastic Australia PTY Limited in 2015"--Title page verso.
"Now a major motion picture from DreamWorks"--Cover.
Keywords: Animals -- Comic books, strips, etc; Heroes -- Comic books, strips, etc; Animals -- Juvenile fiction; Heroes -- Juvenile fiction; Humorous stories; Graphic novels; Animals -- Fiction; Heroes -- Fiction; Humorous stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Comics & Graphic Novels / Animals; Animals; Heroes; Graphic novels; Humorous comics; Humorous fiction; Juvenile works; Fiction; Funny animal comics; Humorous comics; Graphic novels; Juvenile works